2020
DOI: 10.1038/s41598-020-67968-6
|View full text |Cite
|
Sign up to set email alerts
|

Maternal glucose homeostasis is impaired in mouse models of gestational cholestasis

Abstract: Women with intrahepatic cholestasis of pregnancy (ICP), a disorder characterised by raised serum bile acids, are at increased risk of developing gestational diabetes mellitus and have impaired glucose tolerance whilst cholestatic. FXR and TGR5 are modulators of glucose metabolism, and FXR activity is reduced in normal pregnancy, and further in ICP. We aimed to investigate the role of raised serum bile acids, FXR and TGR5 in gestational glucose metabolism using mouse models. Cholic acid feeding resulted in redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…PMΔ5S-induced calcium signals (32), further supporting our results. It is intriguing that a previous study of pregnant Tgr5 -/and Fxr -/mice demonstrated impaired insulin release in vivo, whereas the ex vivo islet studies reported in this manuscript did not show impaired insulin secretion (12). It is possible that there are whole-body differences and compensatory mechanisms in the Tgr5 -/and Fxr -/mice that are not replicated using direct islet stimulations.…”
Section: Trpm3-deficient Ins-1 Cells Also Had Reduced Pmδ5s-induced Gsis As Well As Lackingmentioning
confidence: 59%
See 1 more Smart Citation
“…PMΔ5S-induced calcium signals (32), further supporting our results. It is intriguing that a previous study of pregnant Tgr5 -/and Fxr -/mice demonstrated impaired insulin release in vivo, whereas the ex vivo islet studies reported in this manuscript did not show impaired insulin secretion (12). It is possible that there are whole-body differences and compensatory mechanisms in the Tgr5 -/and Fxr -/mice that are not replicated using direct islet stimulations.…”
Section: Trpm3-deficient Ins-1 Cells Also Had Reduced Pmδ5s-induced Gsis As Well As Lackingmentioning
confidence: 59%
“…Some progesterone sulfates bind receptors that influence lipid, glucose, and bile acid metabolism. The progesterone sulfate 5β-pregnan-3α-20α-diol-sulfate (pregnanediol sulfate [PM3S]) activates the G-protein–coupled bile acid receptor 1 (GPBAR1, or TGR5) ( 11 ), and 5α-pregnan-3β-ol-20-one-sulfate (epiallopregnanolone sulfate [PM5S]) is a partial agonist for the bile acid receptor farnesoid X receptor (FXR) ( 10 ); this may be of relevance to the etiology of GDM, as Fxr −/− and Tgr5 −/− mice have impaired glucose tolerance in pregnancy ( 12 ). Another cholesterol-based sulfated endogenous neurosteroid, 5-pregnen-3β-ol-20-one-sulfate (pregnenolone sulfate [PMΔ5S]), is a well-established modulator of receptors and channels such as transient receptor potential cation channel subfamily M member 3 (TRPM3).…”
Section: Introductionmentioning
confidence: 99%
“…Since both receptors play a role in regulation of glucose homeostasis, changes to normal receptor function are also likely to affect glucose metabolism. Consistent with this, mice deficient of FXR or TGR5 develop gestational impaired glucose tolerance, and FXR -/mice have insulin resistance in pregnancy (135). It is plausible both FXR and TGR5 could contribute to the pathophysiology of GDM and could be the link between the increased risk of developing GDM in ICP women.…”
Section: Impact Of Bile Acids In Icp and Gdmmentioning
confidence: 67%
“…The bile acid receptors FXR and TGR5 are involved in glucose homeostasis. Decreased activity of these receptors and elevated levels of circulating bile acid may contribute to altered glucose metabolism in pregnant women with ICP [ 21 ]. Studies showed that bile acids recognized with G protein-coupled bile acid receptor 1 could induce NF-κB pathway activation, consequently upregulated inflammatory genes in trophoblasts, leading to inflammation and aberrant leukocyte infiltration in placenta [ 22 ].…”
Section: Discussionmentioning
confidence: 99%